Legal Awareness of Village Communities Toward the Formulation of Village Regulations (Perdes) Based on Law No. 6 ff 2014 - Valda Pramudita Erviani; Hananto Widodo (NOVUM : JURNAL HUKUM, 2024)
Bendotretek Village is considered by many local people to be that the village's development is still lagging behind compared to the surrounding villages and village officials (individuals) are considered not optimal in disseminating village regulations, as a result many people who do not know about local village regulations. According to Permendagri 111 of 2014 concerning Technical Guidelines for Village Regulations, article 26 which states "Joint Village Head Regulations are disseminated to the community of each Village." which means that the village community should already know and apply the village regulations that have been ratified and promulgated. The aim of this research is to measure the level of legal awareness of village communities regarding village regulations because village regulations have an important function, namely as a means of upholding justice for village communities. This type of research is an empirical legal research method or an empirical juridical research method, a form of study using subject study, which specifically examines current legal provisions and what the facts are in society. Based on research results, the level of awareness among the Bendotretek Village community is low at 27.5% because many village residents are not aware of the village regulations. Respondents who have legal awareness of Bendotretek village regulations are village officials and stakeholders. Meanwhile, those who do not understand village regulations are people who are indifferent to village regulations.